Changes in Epidemiological Characteristics of Varicella and Breakthrough Cases in Ningbo, China, From 2010 to 2023: Surveillance Study - Xingqiang Pan; Yan Zhang; Xuefei Zhao; Dandan Zhang (JMIR Public Health and Surveillance)
Abstract BackgroundVaricella is a prevalent respiratory infectious disease. Continuous monitoring is essential to understand evolving epidemiological patterns, particularly given the impact of vaccination and recent nonpharmacological interventions. ObjectiveThis study aims to monitor the epidemiological characteristics of varicella and the changes in breakthrough cases to inform adjustments in immunization strategies and enhance prevention efforts. MethodsFrom 2010 to 2023, varicella incidence was monitored using active (2010-2011) and passive (2012-2023) surveillance methods. Data were obtained from the Chinese Center for Disease Prevention and Control’s information system and Ningbo’s Immunization Information System. The study period was divided into four intervals to analyze trends. A birth cohort (2009-2013) was established to examine breakthrough cases. A recurrent neural network model was constructed for deep learning analysis of incidence trends and the impact of nonpharmaceutical interventions. ResultsBetween 2010 and 2023, a total of 70,163 varicella cases were reported in Ningbo. Seasonal distribution indicated two incidence troughs before 2020 and only one from 2020 to 2023. The predominant age of onset was 10‐14 years, accounting for 23.93% (16,795/70,163) of cases. From 2010 to 2013, the highest incidence was among children aged 5‐9 years; from 2014 to 2019, it shifted to those aged 10‐14 years; and from 2020 to 2023, it was primarily among individuals aged 15‐19 years. Following the introduction of a second vaccine dose (2014‐2019), incidence among children younger than 10 years of age decreased, notably by 59.54% in those aged 1‐4 years. Conversely, incidence among individuals aged 10 years and older increased, particularly by 123.78% in the 15‐19 years age group, with a significant upward trend (Ptrend ConclusionsThe significant shifts in varicella epidemiology between 2010 and 2023 highlight the importance of continuous monitoring and proactive immunization adjustments. We recommend enhanced varicella surveillance focusing on adult populations, and a targeted increase in 2-dose vaccine coverage, particularly in high-risk environments such as high schools and universities.